The contribution of accounting and financial information to economic performance - BENGUIRECHE , Mohammed Nabil; ouguenoune, hind (Journal of Research in Finance and Accounting, 2022)
This article aims to study the impact of accounting and financial reporting on economic performance by focusing on particular channels. It is then to think about the interactive way of this impact with other institutional factors. Using a theoretical methodology, in which we have identified three channels involving the use of information, the study concludes that a structure and governance mechanisms adapted to control the quality of accounting and financial information lead to a high level of profitability and consequently reflect a high level of economic performance of the firm.